2018
DOI: 10.1007/s11099-018-0849-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in photosynthesis performance of cassava at two different growth stages under irrigated and rain-fed conditions in a tropical savanna climate

Abstract: Seasonal variations in photosynthesis of cassava cv. Rayong 9 (RY9) under irrigated and rain-fed conditions were evaluated at the age of three and six months after planting (MAP). Photosynthetic light-response (P N /I) curves revealed that cassava leaves attained the highest maximum net photosynthetic rates (P Nmax ) in the rainy season, followed by the hot one, while the lowest P Nmax was found in the cool season. Photosynthetic potential of the 3-month-old plants was mostly higher than that of the 6-month-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 62 publications
(89 reference statements)
2
21
0
Order By: Relevance
“…In the present study, this condition was evidenced by a lower A in the rainy season. However, in the rainy period, the g s and E were higher, which favored stomatal opening as a result of higher RH values and lower values of AT and VPD [52]. Likewise, the positive correlation observed between A and g s and the daytime pattern of these parameters in both periods suggest that both processes lead to a higher photosynthetic performance in the morning hours, where there is greater stomatal openings, favoring higher assimilation rates of CO 2 [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, this condition was evidenced by a lower A in the rainy season. However, in the rainy period, the g s and E were higher, which favored stomatal opening as a result of higher RH values and lower values of AT and VPD [52]. Likewise, the positive correlation observed between A and g s and the daytime pattern of these parameters in both periods suggest that both processes lead to a higher photosynthetic performance in the morning hours, where there is greater stomatal openings, favoring higher assimilation rates of CO 2 [53].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also reported an increase in photosynthesis in the dry period in the Amazon region because water is not a limiting factor, but light is [5557]. Although the dry evapotranspiration period is greater because of an increase in radiation and temperature [49], a partial closure of the stomata would be expected because of a higher VPD [52,58] as compared with the rainy period, possibly because of the deep root system of rubber trees, combined with the hydraulic redistribution of the roots [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…The same leaves were then preadapted to a dark period for one hour by fixing special tags on each leaf blade before measurements were retaken. After one hour of dark adaptation, the sensor cup was fitted on the leaf for measurement of maximum quantum efficiency of photosystem II photochemistry (Fv/Fm) [12,14,[18][19][20][21]. Relative water content (RWC) for those the same leaves as Pn and chlorophyll fluorescence evaluations were recorded between 9.00-10.00 a.m., where 1 cm 2 in leaf area was collected using a leaf disc borer.…”
Section: Soil Moisture Content =mentioning
confidence: 99%
“…Consequently, it resulted in reduced photosynthesis capacity and crop growth [35][36][37]. Likewise, Vongcharoen et al [38] indicated that the lowest leaf photosynthesis of cassava was recorded during the cool season when compared to the rainy and hot seasons, when solar radiation is a limiting factor. Temperatures below 17 • C or above 30 • C inhibited leaf growth and starch yield of cassava, and low relative ambient humidity caused partial stomatal closure, resulting in reduced crop growth [26,37].…”
Section: Discussionmentioning
confidence: 99%